2015
DOI: 10.1155/2015/393124
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Contrast-Enhanced Transabdominal Ultrasonography to Diagnose Early Chronic Pancreatitis

Abstract: Purpose. The purpose of this study was to establish the relationship between the grade of chronic pancreatitis (CP) and pancreatic blood flow as measured by contrast-enhanced transabdominal ultrasonography (CEUS) and to diagnose early CP easily. Methods. This pilot study was conducted in 8 patients with CP, 7 patients with early CP, and 6 control participants. After injecting 0.015 mL/kg of perflubutane by manual bolus, values in one region of interest (ROI) in pancreatic parenchyma and one ROI including the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Pancreatic sarcoidosis may resemble chronic pancreatitis in the presence of fibrotic tissue. Pancreatic blood flow also decreases as pancreatic fibrosis progresses ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic sarcoidosis may resemble chronic pancreatitis in the presence of fibrotic tissue. Pancreatic blood flow also decreases as pancreatic fibrosis progresses ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study showed that the blood flow ratio between the superior mesenteric artery and the pancreatic parenchyma evaluated by CEUS correlates with the grade of chronic pancreatitis and concluded that this safe and convenient method may be useful for the early diagnose of CP [22].…”
Section: Chronic Pancreatitis (Cp)mentioning
confidence: 99%
“…Non-invasive measurements of pancreatic perfusion have been performed by contrast-enhanced ultrasound (CEUS) [ 1 5 ], perfusion Computer tomography (CT) [ 6 , 7 ] and magnetic resonance imaging (MRI) [ 8 ]. Attempts at an in-vivo reference standard have been made using hydrogen gas clearance method under laparoscopy [ 9 ] and endoscopy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the pancreas perfusion can be useful in a clinical setting such as characterizing tumours [ 2 , 15 ] and in the evaluation of other focal pancreatic lesions [ 16 ]. One study was able to demonstrate reduced perfusion in chronic pancreatitis patients compared to healthy controls [ 10 ], and attempts have been made to define perfusion changes in early chronic pancreatitis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%